2007
DOI: 10.1016/s0079-7421(07)48006-9
|View full text |Cite
|
Sign up to set email alerts
|

The Adaptive and Strategic Use of Memory By Older Adults: Evaluative Processing and Value-Directed Remembering

Abstract: Why do we remember some events and not others, and how does this change in old age? Although there are a variety of ways to address this question, the present perspective emphasizes how value can have a profound eVect on how we use our memory to remember certain information. The ability to select and prioritize what information is important to remember, relative to less salient or peripheral information, is an essential skill for the eYcient use of memory. For example, university students seek to memorize info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
217
4

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 163 publications
(246 citation statements)
references
References 121 publications
20
217
4
Order By: Relevance
“…On each trial, participants were presented with a lowreward (1 point), a medium-reward (3 points), and a highreward (5 points) item, and participants had 5 s to select and study the items. An obvious strategy to maximize performance (in terms of points earned) would be to prioritize the 5-point items for study, and previous research indicated that learners typically develop agendas to study highly valued items (Ariel et al, 2009;Castel, 2007;Castel, Farb, & Craik, 2007). Accordingly, we expected that the influence of reading habits would weaken in this context, but participants' study decisions were still largely biased by reading habits, even when participants had a monetary incentive to earn as many points as possible!…”
Section: Discussionmentioning
confidence: 95%
“…On each trial, participants were presented with a lowreward (1 point), a medium-reward (3 points), and a highreward (5 points) item, and participants had 5 s to select and study the items. An obvious strategy to maximize performance (in terms of points earned) would be to prioritize the 5-point items for study, and previous research indicated that learners typically develop agendas to study highly valued items (Ariel et al, 2009;Castel, 2007;Castel, Farb, & Craik, 2007). Accordingly, we expected that the influence of reading habits would weaken in this context, but participants' study decisions were still largely biased by reading habits, even when participants had a monetary incentive to earn as many points as possible!…”
Section: Discussionmentioning
confidence: 95%
“…Specifically, recent research has suggested that test forms may be differentially sensitive to distinctions between positive and negative materials (Zimmerman & Kelley, 2010); thus, the present study could be replicated with cued or free recall testing to examine young and older adults' sensitivity to positive and negative associations. Additionally, given the gender differences observed in our older adult group, it would also be interesting to consider potential gender differences in metamemory and how gender differences may influence memory performance when monitoring and strategy selection are emphasized (e.g., value-directed remembering; Castel, 2008). Finally, given past research that has shown gender differences in functional brain connectivity when processing emotional faces (e.g., Mather, Lighthall, Nga, & Gorlick, 2010), it might be the case that such gender differences in connectivity are important in processing emotional linguistic materials as well.…”
Section: Itemmentioning
confidence: 99%
“…However, the present paradigm is unique in that the messages in the stories are relatively engaging and meaningfully integrated, and some research has shown that age effects in memory are not obtained for more meaningful or goal-related information (see Castel, 2007, for a review).…”
Section: Free Recallmentioning
confidence: 99%